Inclusão socioespacial de pessoas com deficiência: os espaços de morar do programa “Minha Casa Minha Vida” na cidade de Ponta Grossa-PR - Lombardi, Anna Paula (2014)
This dissertation reflects on living spaces of disabled persons focusing on their inclusion into the Brazilian Federal Housing Programme “My house, my life” (= Minha Casa Minha Vida). The analysis is based on primary experiences during the implementation phase of the Programme in Ponta Grossa (Paraná, Brazil) in the neighbourhoods of Jardim Athenas, Jardim Roma, Jardim Gralha Azul, Jardim Boreal, and Jardim Recanto Verde. The formulation of the concept of living spaces used in this research is not reduced to the space of habitation adapted to disabled persons but also interpreted in a broader sense. Thus, subjective elements are included like dignity, family relations and relations with neighbours as well as the guarantee of basic and non-basic needs rights, both in a material and non-material sense. The principal research objective is to evaluate the habitation programme in respect to its effects on social inclusion of disabled persons. Therefore, the perception of research “subjects” has been produced via interviews with the subjects themselves. Hereby, it can be concluded that, in fact, moving to the adapted houses of the programme has caused a higher level of living standard in terms of habitation;however, due to the fact that the peripheral localization of the housing areas and its precarious conditions in respect to both material infrastructure and services, has even caused an increased socio-spatial exclusion of disabled persons.